Association between mismatch negativity and voxel-based brain volume in schizophrenia. Issue 9 (September 2018) - Huang, Wei-Lieh; Liu, Chao-Yu; Liu, Chih-Min; Liu, Hon-Man; Yang, Chung-Yi; Hwang, Tzung-Jeng; Hsieh, Ming H.; Hwu, Hai-Gwo
Highlights: Mismatch negativity (MMN) amplitudes were significantly lower in schizophrenia patients than healthy controls. The volume of left hippocampus is correlated with MMN in schizophrenia patients. Hippocampal volume is related with MMN in schizophrenia patients after controlling for confounders. Abstract: Objective: This study aimed to investigate the association between mismatch negativity (MMN) and volumes of several brain regions measured using a semi-automated method in patients with schizophrenia and healthy controls. Methods: MMN in response to duration deviants and magnetic resonance imaging were acquired from 36 schizophrenia patients and 14 healthy controls. FreeSurfer was used for volumetric analysis. MMN amplitudes, brain volumes and their association were compared between schizophrenia and controls. Correlation analysis and multiple linear regression analysis were used to examine the correlated variables of MMN. Results: MMN amplitude was significantly lower in the schizophrenia group. In schizophrenia, MMN was positively correlated with age and negatively correlated with left hippocampal and right pars opercularis volumes. The association between left hippocampal volume and MMN in schizophrenia remained significant after controlling for potential confounders. Conclusions: Smaller hippocampal volume may play a role in the abnormal manifestation of MMN in schizophrenia. Significance: The significant association between MMN and left hippocampal volume may suggest unique neurobiological contribution of hippocampus in auditory processing in schizophrenia.